Manvia, S.A. Equity Valuation - Santos, Sara José Pinto dos (2022)
This thesis aimed to conduct an equity valuation of Manvia, S.A., based on the calculation of its current shares’ value. Manvia is a company established in 1998, part of the Mota-Engil group. Although the company’s core business is the provision of maintenance services, it also acts in the execution of construction works for both public and private sectors. Manvia's activity can be divided into three major business areas: Facilities, Environment, and Industry. To reach the company’s valuation, we relied on the Free Cash Flow to the Firm (FCFF) one of the Discounted Cash Flows (DCF) methods. Such was done by following certain necessary adaptations, since Manvia is a non-listed company. Due to this, one cannot recur to explicitly available market values, nor to readily available forecasts and assumptions as necessary for constructing the model. The global context of economic, social and political uncertainty which has emerged during our work (augmented by the war in Ukraine) has not been neglected. This was factored in the assumptions and macroeconomic forecasts embedded in Manvia’s valuation, contributing to the final estimates of 7.107.286 euros and a book value per share of 14,21 euros.